1990
DOI: 10.1002/pssb.2221570214
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Surface Magnetization of Fe(110) by Spin‐Polarized Low‐Energy Electron Diffraction

Abstract: a), R. FEDER3) (a), G. WALLER (b), and U. GRADMANN (b) Exchange and spin-orbit scattering asymmetries of spin-polarized low-energy electrons from Fe( 1 10) are measured at room temperature for several beams at constant energies as functions of the polar angle of incidence ("rocking curves"). Corresponding calculations by means of a relativistic multiple scattering formalism gave results in good agreement with the experimental data. The sensitivity of parts of the calculated curves to changes in the layer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…For the uncovered Fe surface (top in figure 3), the surface magnetic moment is enhanced by about 34% with respect to the bulk magnetic moment (2.99 µ B versus 2.24 µ B ). A similar increase was also found for Fe(110) [40] (see also [41] for an overview). Upon coverage with Mn, the maximum magnetic moment in the Fe is shifted from layer 0 to layer −1, with the increase reduced to about 12%.…”
Section: Magnetic Profilessupporting
confidence: 78%
“…For the uncovered Fe surface (top in figure 3), the surface magnetic moment is enhanced by about 34% with respect to the bulk magnetic moment (2.99 µ B versus 2.24 µ B ). A similar increase was also found for Fe(110) [40] (see also [41] for an overview). Upon coverage with Mn, the maximum magnetic moment in the Fe is shifted from layer 0 to layer −1, with the increase reduced to about 12%.…”
Section: Magnetic Profilessupporting
confidence: 78%
“…The Fe atoms of the topmost layer have a higher magnetic moment when compared to the bulk value. This finding is known for magnetic atoms on surfaces and is related to the band narrowing of the d-states [36,37]. The trend for the decrease of the spin magnetic moments going to deeper Fe layers is similar for LSDA and LSDA+DMFT calculations.…”
Section: A Electronic Structure Calculationsupporting
confidence: 68%
“…Ky,78.20.Ls The influence of the dimensionality on magnetism has been widely studied during the past years. A general trend is that the magnetic moment in ferromagnets like Fe, Co, and Ni is enhanced with reduced coordination number [1]: It was found that the magnetic moment of the free surface is enlarged with respect to that of the bulk [2][3][4][5]. From the enhanced moment at rough surfaces on Fe(110) Albrecht et al derived the magnetic moment for atoms at step sites to be larger by roughly 0.5m B than for those in the flat surface at T 300 K [6,7].…”
mentioning
confidence: 99%